Hospital Opioid Requirements Following Continuation Versus Discontinuation of Buprenorphine for Addiction – A Retrospective Cohort Study. (2nd October 2019) - Houchard, Gary; Kullgren, Justin; Saphire, Maureen; Porter, Kyle; Abel, Stephanie
Abstract: Evidence guiding inpatient management of buprenorphine is lacking—this retrospective cohort study evaluated the clinical impact of hospital continuation versus discontinuation of buprenorphine at an academic medical center. The primary outcome was inpatient oral morphine equivalents (OME). Secondary outcomes included patient pain levels, functional assessment, and hospital length of stay. One hundred thirty-one patients (74 continued buprenorphine, 57 discontinued) were included in the analysis. Median OME were significantly lower among patients continued on buprenorphine versus discontinued (11 mg vs 103 mg, p  < 0.001), as was maximum 24-hour opioid utilization (60 mg vs 240 mg, p  < 0.001) and 24-hour pre-discharge utilization (10 mg vs 128 mg, p  < 0.001). Median pain levels were similar between groups at the time of admission (8 in each group, p  = 0.48), discharge (7 in each group, p  = 0.26), and over the first 7 days of hospitalization (7 vs 8, p  = 0.08). Hospital length of stay was similar between groups (5 days in each group, p  > 0.99). Failure to reinitiate buprenorphine occurred in 31/57 patients (54.4%) in the discontinuation group. Hospital buprenorphine continuation is associated with reduced opioid requirements, while not significantly impacting pain levels, functionality, or length of admission. Failure to reinitiate buprenorphine was common and may have negative implications for addiction treatment.